Investigating faculty adoption of Blended Learning - Md Ghalib, Mohd. Feham; Mat Daud, Nuraihan; Sahrir, Muhammad Sabri (Pusat Pengajaran & Teknologi Pembelajaran, Universiti Kebangsaan Malaysia, 2014)
A combination of face-to-face (f2f) instruction with Web-based delivery helps to meet the needs of diverse learners. Various terms have been used to refer to this combination of approaches. These include Blended Learning, hybrid learning, mixed mode learning, mediated learning, hybrid instruction, web-assisted instruction and web-enhanced instruction (Delialioglu & Yildirim, 2007; Gulbahar & Madran, 2009; Bonk, 2004). According to Dziuban, et al. (2004), which term to use, is a matter of preference. The terms are used interchangeably, and may be used to define one another. Colin and Moonen (2001), for example, define Blended Learning as "a hybrid of traditional face-to-face and online learning so that instruction occurs both in the classroom and online, and where the online component becomes a natural extension of traditional classroom learning" (Colis & Moonen, 2001 cited in Rovai & Jordan, 2004, p.3)